The Concept of Aesthetic Existence in S. Kierkegaard’s Philosophy - Šliogeris, Arvydas (Problemos, 1978)
The aesthetic medium and aesthetic type of human existence in S. Kierkegaard’s philosophy is discussed. The author points out the inadequacy of reducing the aesthetic type of existence merely to psychological phenomena and reveals the ontological trend of the Kierkegaardian interpretation of aestheticism. The deep connection between the phenomenon of aestheticism and socio-economic processes in the Western Europe of the 19th century is traced.